Family Connect: The Pilot Test of a Cross-Systems Behavioral Health Treatment Referral and Linkage Intervention for Youth on Probation - Elkington, Katherine S. (Criminal justice and behavior, 2023)
Despite high rates of substance use, youth involved in the juvenile justice system are unlikely to be linked to the treatment services they need. Family Connect is a flexible, family-focused, linkage intervention developed to address multilevel barriers and increase youth engagement in care through the introduction of a linkage specialist. We describe the components of Family Connect and present findings from the intervention pilot test comparing 18 youth–caregiver dyads to 95 historical controls on referral, attending intake and initiating treatment. Results indicated preliminary support for Family Connect as an approach to increase cross-systems linkage and access to behavioral health care. Findings also suggested support for the feasibility of the intervention and indicated that justice-involved youth and their caregivers found the intervention to be acceptable. In addition to discussing our findings in the context of recent justice reforms, and the importance of improving access to treatment, we make recommendations to inform a future trial of Family Connect.